Interactive Self-Reporting as Behavioural Cue Elicitor for Online-Classroom Assessment - Hao Xu (Behavioral Sciences, 2022)
How teachers should elicit and draw on behavioural cues for online-classroom assessment is of much interest to both researchers and practising teachers. Aiming to explore how to enhance interactive self-reporting as a behavioural cue elicitor for online-classroom assessment, this study adopted a large-scale questionnaire survey to investigate the effects of the intensity of interaction in interactive self-reporting and teachers’ professional experience on the quality of assessment data in online teaching. Results showed that only the intensity of teacher’s follow-up interaction regarding interactive self-reporting had a significant impact on the quality of the assessment data. Specifically, as a behavioural cue elicitor, interactive self-reporting may be best utilised when interaction of a moderate intensity is employed by the teacher following students’ self-report. The accuracy and efficiency of interactive self-reporting as a means to obtain assessment data in online teaching can only, thus, be best synergised. Otherwise, the accuracy and efficiency may be reduced to a wax-and-wane relationship, i.e., each one increases at the expense of the other.